African development, African transformation how institutions shape development strategy - Landry Signe&#769 (New York, NY Cambridge University Press, 2018)
Introduction : NEPAD and Africaʹs transformation in the twenty-first century -- An analytical framework to explain the origin, development, and effect of NEPAD -- The foundations and first generations of structural adjustment programs -- Partial reorientation of International Monetary Fund and World Bank discourse and the creation of NEPAD -- NEPAD and international financial institutions : change or continuity? -- NEPAD in the twenty-first century : evolution, implementation of key programs, institutional development, and inter-state cooperation -- Financing Africaʹs development in the twenty-first century : assessment and perspectives of NEPADʹs resource mobilization strategy -- The way forward to transforming Africa by 2030/2063 : resource mobilization, financing, and capacity-building strategies for effective delivery of the sustainable development goals and the African Union Agenda 2063 -- Conclusion : continental development fifteen years after the creation of NEPAD : theoretical and practical implications.
Includes bibliographical references and index
Keywords: New Partnership for Africa's Development